2006
DOI: 10.1161/circulationaha.105.000901
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Toll-like Receptor 4 With Eritoran Attenuates Myocardial Ischemia-Reperfusion Injury

Abstract: Background-We previously reported that the functional mutation of Toll-like receptor 4 (TLR4) in C3H/HeJ mice subjected to myocardial ischemia-reperfusion (MI/R) injury resulted in an attenuation of myocardial infarction size. To investigate the ligand-activating TLR4 during MI/R injury, we evaluated the effect of eritoran, a specific TLR4 antagonist, on MI/R injury, with the goal of defining better therapeutic options for MI/R injury. Methods and Results-C57BL/6 mice received eritoran (5 mg/kg) intravenously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
170
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(187 citation statements)
references
References 24 publications
6
170
1
5
Order By: Relevance
“…However, there was no statistically significant difference among the patients groups. Finally, the minor allele frequencies of both TLR4 variants are rather low as reported previously (16,23,24). Consequently, the frequency of the rs4986790 and rs47986791 haplotype is even lower.…”
Section: Wild Typesupporting
confidence: 61%
See 1 more Smart Citation
“…However, there was no statistically significant difference among the patients groups. Finally, the minor allele frequencies of both TLR4 variants are rather low as reported previously (16,23,24). Consequently, the frequency of the rs4986790 and rs47986791 haplotype is even lower.…”
Section: Wild Typesupporting
confidence: 61%
“…Loss of TLR4 in knock-out mouse models showed the protective effects in several types of heart failure to include myocardial ischemia, pressure overload, viral myocarditis, and toxic cardiomyopathy (11)(12)(13)(14)(15). Moreover, pharmacological inhibition of TLR4 in mouse models of myocardial ischemia exerts beneficial therapeutic effects (16). In patients with coronary artery disease, the peripheral contents of TLR4-positive monocytes were significantly increased during acute myocardial ischemia (17).…”
Section: Dilated Cardiomyopathy (Dcm)mentioning
confidence: 99%
“…Thus, through mediation of endothelial actin cytoskeleton, TLR4 may be an important effector of IRI-induced edema in humans, and the TLR4 receptor may be a promising target for pharmacological intervention to mitigate IRI and other forms of acute lung injury. Pretreatment of mice with eritoran, another TLR4 inhibitor, reduced myocardial infarction size in a murine model of cardiac IRI (41). It is possible that CRX-526 may have effects on other receptors or pathways besides TLR4, but our in vivo data in HeJ and TLR4Ϫ/Ϫ mice clearly show that functional TLR4 substantially contributes to IRI-induced pulmonary edema.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, Michelsen et al showed that lack of TLR4 results in reduction of atherosclerosis in mice [29]. A study showed that direct inhibition of TLR4 could significantly reduce the detrimental effects of myocardial ischemia reperfusion [30]. Those findings were further supported by the point, thath TLR4 deficiency leads to alteration in lipid content of atherosclerotic plaque and reduces macrophage infiltration.…”
Section: Discussionmentioning
confidence: 94%